Clinical and pathogenic aspects of vibrational disease and comorbid pathologies. - V. A. Kapustnyk; O. L. Arkhipkina; L. A. Poliakova; N. K. Sukhonos (Medičnì Perspektivi)
Despite the tendency to decrease in the level of vibrational disease morbidity, this pathology is third in the structure of occupational diseases in Ukraine. According to research design, we have examined 178 vibrational disease patients of I and II degree due to local vibration. They have been divided into 3 groups: first — 66 patients with vibrational disease and chronic obstructive pulmonary disease; second — 60 patients with vibrational disease and arterial hypertension of II degree, and group of comparison – 52 patients with isolated course of vibrational disease. We have used clinical and physiological, ELISA methods to estimate cytokines levels in these patients. We have found that clinical signs of vibrational disease depend on vibrational disease progressing and comorbid pathologies. Overlay of chronic obstructive pulmonary disease to vibrational disease significantly worsens disease course, manifested by augmenting of clinical symptoms, neurovascular and trophic violations. Comorbid course of vibrational disease and arterial hypertension leads to respective worsening of cardio-vascular pathology. One of the mechanisms of development and progressing of vibrational disease is imbalance of cytokine chain of immunity — increase of the amount of inflammatory cytokine TNF-α and decrease of anti-inflammatory — IL-10. Overlay of chronic obstructive pulmonary disease enhances this trend. In patients with comorbid course of vibrational disease and arterial hypertension we have observed development of secondary dysregulatory state of immunocompetent system. This is proved by increased levels of inflammatory cytokines (TNF-α by 62.5 % and IL-8 by 46.5 %), and decreased activity of melatonin by 35.0 % in comparison with group of patients with isolated vibrational disease.